The Impact of Natural Gas Prices on Production by Industries in Slovenia (Lex localis - Journal of Local Self-Government, 2009)
Article empirically investigates how intensive is the impact of natural gas prices on production by industries in Slovenian economy. Natural gas price movements can help us in forecasting the movements in electricity, natural gas, steam, hot water supplies, the production of metals, textiles, leather, footwear, leather and fur products, clothes, the production of pulp, paper, cardboard and products from paper and cardboard, the production of products from rubber and plastic materials, processing industry and the production of furniture, the production of intermediary consumption products and recycling. We proved that natural gas prices increase for 1 % point contributes to higher prices of living necessaries for 0,005 % points.KEYWORDS: • natural gas prices • gas quantities • production by industries • Slovenia